FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY YANG DIMODERASI OLEH PROFITABILITAS PADA PERUSAHAAN SUB MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2013 – 2017 - Endang Masitoh, Devina Rizki Amelia, Yuli Chomsatu & (Universitas Slamet Riyadi, 2018)
This research aims to know the factors that affect the audit delay are moderated by the profitability of the company in the automotive and manufacturing of components sub listed in Indonesia stock exchange year 2013 – 2017. Method of determination of the sample using a purposive sampling by the number of samples that used as many as 35 of the financial statements. The results of the testing show that the size of the company, the auditor's opinion, the size of the hood, the operating loss, profit and profitability had no effect against the audit delay while the leverage effect on the audit delay. The size of the company, the auditor's opinion, the size of the hood, the operating income that profitability was able to moderate the (weakened) on auditing delay while the leverage that profitability was able to moderate the (increased) in the audit delay. Keywords: company size, leverage, auditor opinion, size the accounting firm, operating profit, profitability, audit delay.